1997
DOI: 10.1161/01.cir.96.10.3617
|View full text |Cite
|
Sign up to set email alerts
|

Na + /H + Exchanger Activity Does Not Contribute to Protection by Ischemic Preconditioning in the Isolated Rat Heart

Abstract: Because coadministration of HOE (at a concentration sufficient to inhibit NHE activity) did not reduce the efficacy of PC in either protocol, we conclude that NHE activity does not contribute to the cardioprotective actions of PC. On the contrary, NHE inhibition during the prolonged ischemic period may enhance the protection afforded by PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
4

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 30 publications
4
49
4
Order By: Relevance
“…It is conceivable that the effects of Na ϩ /H ϩ exchange inhibition on ischemic contracture or reperfusion-induced arrhythmias exist for only a lesser degree of ischemic damage. In accordance with the present report, selective inhibition of Na ϩ /H ϩ exchange did not attenuate ischemic contracture during Ն40 minutes of no-flow ischemia in isolated buffer-perfused rat hearts 25 or in bloodperfused rabbit hearts. 8 Although there were significant differences for [Ca 2ϩ ] i during ischemia, ischemic contracture was virtually identical in both groups ( Figures 1B and 1F).…”
Section: ؉ Overload and Ph I On Reperfusionsupporting
confidence: 93%
“…It is conceivable that the effects of Na ϩ /H ϩ exchange inhibition on ischemic contracture or reperfusion-induced arrhythmias exist for only a lesser degree of ischemic damage. In accordance with the present report, selective inhibition of Na ϩ /H ϩ exchange did not attenuate ischemic contracture during Ն40 minutes of no-flow ischemia in isolated buffer-perfused rat hearts 25 or in bloodperfused rabbit hearts. 8 Although there were significant differences for [Ca 2ϩ ] i during ischemia, ischemic contracture was virtually identical in both groups ( Figures 1B and 1F).…”
Section: ؉ Overload and Ph I On Reperfusionsupporting
confidence: 93%
“…Different and independent mechanisms are believed to confer the IS-reducing effects of Na ϩ /H exchange inhibition (3,38) and ischemic PC (29): Na ϩ /H ϩ exchange inhibition, assumed to protect ischemic myocardium via a delay of intracellular sodium and, subsequently, calcium accumulation (18,20,31), exhibits additional IS reduction when combined with ischemic PC (5, 13) and does not abolish the protective effects of PC when the exposure to a Na ϩ /H ϩ exchange inhibitor is limited to the duration of the PC stimulus (40). On the other hand, inhibitors of the PC pathway, namely, inhibitors of protein kinase C translocation (41,30), adenosine receptor antagonists (12), or inhibitors of ATP-dependent potassium channels (12,15), do not diminish IS reduction by Na ϩ /H ϩ exchange inhibition.…”
Section: /H ϩ Exchange Inhibition and Ischemic Pc: Two Different And mentioning
confidence: 99%
“…It is notable that both of the previous studies that have shown additive benefit with the combination of Na ϩ /H ϩ exchange inhibition and ischemic preconditioning were carried out in rat hearts 12,17 and that no similar additive effect has been observed in the rabbit. 15,16 At first consideration, this might appear to indicate species-specific responses, with Na ϩ /H ϩ exchange inhibition and ischemic preconditioning possessing distinct mechanisms of action in the rat but sharing a common mechanism of action in the rabbit.…”
Section: Na ؉ /H ؉ Exchanger Inhibition and Ischemic Preconditioning:mentioning
confidence: 92%
“…A number of studies have addressed this issue, again by using pharmacological inhibitors to suppress Na ϩ /H ϩ exchanger activity at various times during the experimental protocol: during the cycles of triggering ischemia, 12,13 during index ischemia, 9,12,14 -16 or during both periods. 17 Although contradictory findings have also been reported, 13,14 the majority of these studies 9,12,[15][16][17] have shown that the cardioprotective benefit of ischemic preconditioning is not attenuated by Na ϩ /H ϩ exchange inhibition, indicating that an active exchanger is not necessary to achieve such benefit. To the contrary, in some studies, 12,17 the combination of Na ϩ /H ϩ exchange inhibition with ischemic preconditioning has been shown to provide an additive benefit, with the limitation of infarct size 17 or the improvement in the recovery of contractile function 12 appearing to be significantly greater with the combined intervention relative to either intervention alone.…”
Section: Na ؉ /H ؉ Exchanger Inhibition and Ischemic Preconditioning:mentioning
confidence: 99%
See 1 more Smart Citation